Factorial combinations of protein interactions generate a multiplicity of florigen activation complexes in wheat and barley. (6th September 2015) - Li, Chengxia; Lin, Huiqiong; Dubcovsky, Jorge
Summary The FLOWERING LOCUS T (FT) protein is a central component of a mobile flowering signal (florigen) that is transported from leaves to the shoot apical meristem (SAM). Two FT monomers and two DNA‐binding bZIP transcription factors interact with a dimeric 14‐3‐3 protein bridge to form a hexameric protein complex. This complex, designated as the 'florigen activation complex' (FAC), plays a critical role in flowering. The wheat homologue of FT, designated FT1 (= VRN3), activates expression of VRN1 in the leaves and the SAM, promoting flowering under inductive long days. In this study, we show that FT1, other FT‐like proteins, and different FD‐like proteins, can interact with multiple wheat and barley 14‐3‐3 proteins. We also identify the critical amino acid residues in FT1 and FD‐like proteins required for their interactions, and demonstrate that 14‐3‐3 proteins are necessary bridges to mediate the FT1–TaFDL2 interaction. Using in vivo bimolecular fluorescent complementation (BiFC) assays, we demonstrate that the interaction between FT1 and 14‐3‐3 occurs in the cytoplasm, and that this complex is then translocated to the nucleus, where it interacts with TaFDL2 to form a FAC. We also demonstrate that a FAC including FT1, TaFDL2 and Ta14‐3‐3C can bind to the VRN1 promoter in vitro. Finally, we show that relative transcript levels of FD‐like and 14‐3‐3 genes vary among tissues and developmental stages. Since FD‐like proteins determine the DNA specificity of the FACs, variation in FD‐like gene expression can result in spatial and temporal modulation of the effects of mobile FT‐like signals.